PENYELESAIAN SENGKETA HAK KEKAYAAN INTELEKTUAL DALAM DUNIA MAYA MELALUI BADAN ARBITRASE - Happy Yulia Anggraeni; Fitri Jihad Aminah (Yuriska: Jurnal Ilmiah Hukum, 2023)
Intellectual property rights must be protected by the state and respected by everyone. Along with the development of technology and information, violations of intellectual property rights often occur in cyberspace. However, the IPR Law still needs to provide complete protection and remedy for IPR crimes in cyberspace. Meanwhile, settlement through arbitration of IPR disputes is handled based on the jurisdiction of the countries of each party. This research is normative, using statutory, conceptual, and case approaches. The sources of this research material are primary and secondary materials. Based on the study results, the settlement of intellectual property rights disputes in the country's common law is different in each country, as the United States filed an arbitration effort if there is a clause in advance. If not, then it can be submitted in writing. Meanwhile, in England, there are no strict rules regarding IPR disputes through arbitration. Australia also has the same rules as the UK. Whereas in Switzerland, the settlement of IPR disputes through arbitration is not subject to any law. The most IPR dispute cases in Indonesia were trademark cases, reaching 267 patients from 2018-2022. The arbitration settlement mechanism is very effective because the settlement is carried out based on an agreement, and the parties choose the compensation, thus prioritizing a win-win solution. IPR dispute resolution can be resolved through litigation and non-litigation. The non-litigation route usually chosen is the arbitration route. Arbitration is a very reasonable effort because the solution is confidential, fast and low cost. It can also be used for parties with different jurisdictions. Particularly for IPR violations in cyberspace, the institution authorized as a settlement other than arbitration is the PPND institution